Analysis of the Effect of Regional Original Income and Fund Transfers on City Government Economic Growth in North Sumatra Province - Azizah, Azizah; Sirojuzilam, Sirojuzilam; Amalia Fachrudin, Khaira (Publisher Cv. Inara, 2022)
The objectives of this study are to: 1) Analyze the effect of Local Original Income on the economic growth of the North Sumatra Provincial Government. 2) Analyzing the effect of the General Allocation Fund on the economic growth of the North Sumatra Provincial Government. 3) Analyzing the effect of the Special Allocation Fund on the economic growth of the North Sumatra Provincial Government. 4) Analyzing the effect of Revenue Sharing Funds on the economic growth of the North Sumatra Provincial Government. 5) Analyzing the effect of Regional Original Revenue, General Allocation Fund, Special Allocation Fund, and Revenue Sharing Fund together on the economic growth of the North Sumatra Provincial Government. Tests using panel data analysis can be done with three models, namely Common Effect Model (CEM), Fixed Effect Model (FEM) and Random Effect Model (REM). Tests were carried out with the Chow test, Hausman test, and Langrangge Multiplier test. Based on the results of hypothesis testing in table 4.6, the lower left shows the Prob value (F-statistic) of 0.000000. Prob value. < significance value (0.05). This probability value becomes the basis for accepting Ha which states that simultaneously (together) all independent variables (PAD, DAU, DAK, and DBH) have a significant effect on the dependent variable (economic growth). A positive value on the F-statistic shows that simultaneously PAD, DAU, DAK, and DBH have a positive effect on economic growth.